2015
DOI: 10.1515/jpem-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Familial dysalbuminemic hyperthyroxinemia in a 4-year-old girl with hyperactivity, palpitations and advanced dental age: how gold standard assays may be misleading

Abstract: Here we report the case of a young girl who had vague signs and symptoms potentially attributable to hyperthyroidism and was found to have autoimmune thyroiditis and hyperthyroxinemia. The elevated serum free thyroxine levels were persistent when measured by both standard assays and equilibrium dialysis/high-pressure liquid chromatography-tandem mass spectrometry. The clinical symptoms, with discordant thyroid test results, created a diagnostic dilemma that led initially to unnecessary additional evaluations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Finally, it should be noted that FDH-T4, which does not call for treatment, could mask the simultaneous presence of true thyroid disease such as hypothyroidism, autoimmune thyroiditis, or thyrotoxicosis ( 1 , 2 , 26 , 27 ).…”
Section: Diagnosis Of and Differential Diagnosis To Fdh-t4mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it should be noted that FDH-T4, which does not call for treatment, could mask the simultaneous presence of true thyroid disease such as hypothyroidism, autoimmune thyroiditis, or thyrotoxicosis ( 1 , 2 , 26 , 27 ).…”
Section: Diagnosis Of and Differential Diagnosis To Fdh-t4mentioning
confidence: 99%
“…To these numbers can be added some of the cases with more than one diagnosis referred to in Section “ Diagnosis of and Differential Diagnosis to FDH-T4 .” Thus, three members of a family have both FDH-T4 and congenital hypothyroidism ( 26 ). In another family, a young girl has autoimmune thyroid disease as well as FDH-T4, whereas her father has only FDH-T4 ( 27 ); he is included in Table 1 . Geographically, this type of FDH-T4 has been detected in North America, Western Europe, Eastern Asia, and in New Zealand.…”
Section: Fdh-t4 Causing Mutationsmentioning
confidence: 99%
“…The mutation involves codon 218, which is normally arginine, and it gets replaced with histidine, proline, or serine (or codon 222), which is also arginine that gets replaced with isoleucine. These mutations in the codon 218 and codon 222 for a smaller amino acid reduces the steric hindrances and creates a high-affinity binding site for T4 [ 2 , 9 ]. Individuals with FDH are heterozygous for the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm or better delineate an abnormal result, direct equilibrium dialysis is the next test of choice, as it was in our patient. While this method has a better ability to accurately report true free T4 values in the face of confounding variables, false-positives may still occur [ 9 ]. Hoshikawa et al have reported false-positive results of elevated free T4 assays using equilibrium dialysis/radioimmunoassay (RIA), and they suggest that this assay is not an ultimate standard for diagnosing FDH, especially in patients with the R218P mutation of the ALB gene [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This relatively low T 4 and T 3 differentiates individuals with both conditions from those with classic Graves’ disease. Once hyperthyroidism is treated and the TSH stabilizes, the free T 4 concentration may remain falsely elevated due to accuracy of free T 4 methods when binding proteins are extremely low (19, 20). Measuring free T 4 by direct equilibrium dialysis bypasses these issues.…”
Section: Discussionmentioning
confidence: 99%